Micro-push-out bond strength of Mineral-based root canal sealer in canals with different tapers - Nunna Vasavi; Kantheti Sirisha (Universidad de Concepción., 2021)
Objective: The aim of this study was to assess the micro-push-out bond strength of a mineral-based root canal sealer, BioRoot RCS in canals prepared by K3XF rotary systems of two different tapers. Material and Methods: Eighty caries free maxillary central incisors were used in this study. The samples were allocated into 4 groups (n=20) according to the root canal sealer and taper of the rotary instruments. The samples were obturated using single cone obturation technique. From each root 1mm thick slices at coronal, middle and apical thirds were collected using hard tissue microtome under continuous water coolant. Push-out tests were done for these sections using a Universal testing machine (INSTRON 8801) at a crosshead speed of 1mm/min. One-way analysis of variance (ANOVA) was used to compare the bond strengths within groups and Tukey's multiple post hoc analysis was used for pair-wise comparison of bond strengths. Results: AH Plus exhibited higher micro-push-out bond strength than BioRootRCS though they did not differ significantly (p>0.05). Preparation of root canals with 6% taper rotary instruments showed higher bond strength than 4% though they did not differ significantly (p>0.05). Conclusion: There was no significant difference between micro-push-out bond strength values of BioRoot RCS and AH Plus. The bond strength values were high in 6% taper canals than 4% canals though the difference was not significant statistically.